(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Tahe phytochemical constituents from the ethyl acetate extracts of seed and stem of Anethum sowa were identified by qualitative and gas chromatography-mass spectroscopy (GC-MS). Qualitative analyses exhibited the presence of alkaloids, flavonoids, tannins, carbohydrate, steroids and terpenoids in both extracts. In GC-MS analysis of A. sowa 6 notable peaks (3,4,4a,5,6,7,8,9-Octahydro-2H-benzocyclohepten-2-one, 2,2,4,6,7-Pentamethyl- 1,2,3,4-tetrahydro quinoline, 5-Ethyl-2-methyl-pyridin-4-amine, 2-(2-Furyl) pyridine, 9-Ethyl 9-borabicyclo-[3.3.1]- nonane and 7-Methylenebicyclo-[4.2.0]-octane) and 5 significant peaks (3-Cyclopentyl-1-propyne, 2,2,4,6,7- Pentamethyl-1,2,3,4-tetrahydroquinoline,3,4,4a,5,6,7,8,9-Octahydro-2H-benzocyclohepten-2-one, 1,5-Naphthy-ridin- 2-amine and Octahydro-4,7-methano-5H-inden-5-one) with comparatively higher peak area (%) among 26 and 23 compounds were detected from the ethyl acetate extract of stem and seed respectively. The study encapsulates the information regarding the phytochemical constituents present in the extracts which may have pharmacological importance. Dhaka Univ. J. Pharm. Sci. 16(2): 187-194, 2017 (December)